Mechanisms regulating target gene selection by the homeodomain-containing protein Fushi tarazu. - Nasiadka, A.; Grill, A.; Krause, H.M. (Development, 2000)
Homeodomain proteins are DNA-binding transcription factors that control major developmental patterning events. Although DNA binding is mediated by the homeodomain, interactions with other transcription factors play an unusually important role in the selection and regulation of target genes. A major question in the field is whether these cofactor interactions select target genes by modulating DNA binding site specificity (selective binding model), transcriptional activity (activity regulation model) or both. A related issue is whether the number of target genes bound and regulated is a small or large percentage of genes in the genome. In this study, we have addressed these issues using a chimeric protein that contains the strong activation domain of the viral VP16 protein fused to the Drosophila homeodomain-containing protein Fushi tarazu (Ftz). We find that genes previously thought not to be direct targets of Ftz remain unaffected by FtzVP16. Addition of the VP16 activation domain to Ftz does, however, allow it to regulate previously identified target genes at times and in regions that Ftz alone cannot. It also changes Ftz into an activator of two genes that it normally represses. Taken together, the results suggest that Ftz binds and regulates a relatively limited number of target genes, and that cofactors affect target gene specificity primarily by controlling binding site selection. Activity regulation then fine-tunes the temporal and spatial domains of promoter responses, the magnitude of these responses, and whether they are positive or negative.